Processing 4th generation titanium aluminides via electron beam based additive manufacturing – characterization of microstructure and mechanical properties - Reith, M.; Franke, M.; Schloffer, M.; Körner, Carolin (Materialia, 2020)
Lightweight intermetallic γ-titanium aluminides (TiAl) based alloys are used for high temperature applications in advanced aerospace and automotive engines. Normally, these alloys are processed via investment casting as well as wrought processing, e.g. hot-forging. The feasibility of processing γ-TiAl via electron beam powder bed fusion (PBF-EB/M) is already demonstrated for various titanium aluminides. Due to the high reactivity of titanium aluminides, electron beam powder bed fusion is a promising manufacturing technique which provides dense components with only small variations in the aluminum (Al) content when using accurately optimized process parameters. However, the processing and machining of γ-TiAl based alloys is challenging due to their high reactivity as well as low ductility and fracture toughness at room temperature (RT). The present paper is focusing on the characterization of a 4th generation γ-TiAl based alloy with the nominal composition Ti–47.5Al–5.5Nb–0.5 W (at.%), customized for additive manufacturing process. The high amount of aluminum ensures a peritectic solidification and improves the room temperature ductility. Niobium and Tungsten provide sufficient high temperature strength and creep resistance. However, the processability of a novel alloy via PBF-EB/M is challenging. Therefore, accurately optimized PBF-EB/M parameters are used for the processing of this 4th generation γ-TiAl powder in order to avoid defects and inhomogeneous microstructures. The subsequent material characterization is based on numerous cylindrical specimens additively manufactured in 0°, 45°, and 90° orientation. Micrographs reveal a non-directional NLγ+βo microstructure consisting of lamellar α2/γ colonies, globular γ, and βo-phase. It is shown, that the microstructure possesses no directional dependence for any specimen. Tensile tests are performed at RT, 300 °C and 850 °C with samples in PBF-EB/M state and after hot isostatic pressing. The tensile tests show a room temperature ductility of up to 2.1% and high temperature strength around 380 MPa. Additionally, a minimum creep rate of 1.0 × 10−8 s−1 can be derived from the creep tests at 750 °C with 150 MPa load.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Additive manufacturing; Creep; Mechanical properties; Tensile test; Titanium aluminides